If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8z + 12z = 5z + -21 Combine like terms: 8z + 12z = 20z 20z = 5z + -21 Reorder the terms: 20z = -21 + 5z Solving 20z = -21 + 5z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-5z' to each side of the equation. 20z + -5z = -21 + 5z + -5z Combine like terms: 20z + -5z = 15z 15z = -21 + 5z + -5z Combine like terms: 5z + -5z = 0 15z = -21 + 0 15z = -21 Divide each side by '15'. z = -1.4 Simplifying z = -1.4
| 3x+x+4=8x-4x+4 | | 5(w+4z)-5(w+3)=8 | | 4+6r-r=-5+8r | | x+9=-17 | | 10x+x=196 | | (1/4)(p)+6=8 | | 6x+39x-7=9(5x+6) | | 4x-10=14+x | | 35=7(z)-7 | | 8(n)+16=24 | | 8.2x-2.1x=-122 | | 2(x+5)=4x+6-2x+4 | | 9x=2.25 | | -8=3(y)-2 | | 5(h)-13=12 | | 12x^3=27x^2+15x | | 6k-1-7=10 | | 7x-2=5x+8 | | 6=42-5q-q^2 | | 3x-1/(2)=10 | | -6a-5a=11 | | 3x-1/2=10 | | 2=3(a)+8 | | (3x^2+7x-20)/(x+5) | | graphy=.5x+.5 | | -8x-3x=11 | | 9x+15x-8=6(4x+5) | | -3(d)+10=43 | | t+6t+9=0 | | -2=1+6x-3x | | 25x^2-20x-19=0 | | -6b^2+1b+3=0 |